2009
DOI: 10.1111/j.1398-9995.2008.01765.x
|View full text |Cite
|
Sign up to set email alerts
|

A specific mixture of short‐chain galacto‐oligosaccharides and long‐chain fructo‐oligosaccharides induces a beneficial immunoglobulin profile in infants at high risk for allergy

Abstract: This study shows that GOS/FOS supplementation induces a beneficial antibody profile. GOS/FOS reduces the total Ig response and modulates the immune response towards CMP, while leaving the response to vaccination intact. This suggests that oral GOS/FOS supplementation is a safe method to restrain the atopic march.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
117
1
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(136 citation statements)
references
References 12 publications
5
117
1
8
Order By: Relevance
“…Nowadays cow-milk derived infant formulas are therefore often supplemented with affordable non-digestible carbohydrates (NDCs) such as galacto-oligosaccharides (GOS) and fructo-oligosaccharides (FOS) to substitute for some of the HMO functions (Vandenplas et al 2015). Although beneficial effects of these carbohydrate supplementations have been reported on prevention of allergy and atopic dermatitis (Hoffen et al 2009;Rijnierse et al 2011), it remains largely unclear by which mechanisms these effects are accomplished. Furthermore, there are more potentially beneficial NDCs available which might be suitable for the supplementation of infant formulas.…”
Section: Ndcs To Replace Hmos In Infant Formula: Effects On Microbiotmentioning
confidence: 99%
“…Nowadays cow-milk derived infant formulas are therefore often supplemented with affordable non-digestible carbohydrates (NDCs) such as galacto-oligosaccharides (GOS) and fructo-oligosaccharides (FOS) to substitute for some of the HMO functions (Vandenplas et al 2015). Although beneficial effects of these carbohydrate supplementations have been reported on prevention of allergy and atopic dermatitis (Hoffen et al 2009;Rijnierse et al 2011), it remains largely unclear by which mechanisms these effects are accomplished. Furthermore, there are more potentially beneficial NDCs available which might be suitable for the supplementation of infant formulas.…”
Section: Ndcs To Replace Hmos In Infant Formula: Effects On Microbiotmentioning
confidence: 99%
“…Some nondigestible oligosaccharides are called prebiotics, because they stimulate the growth of commensal bacteria known to be beneficial to the host (38). It has been shown that infant formula including specific nondigestible carbohydrates, like shortchain galactooligosacharides (scGOS) and long-chain fructooligosaccharides (lcFOS), affects the incidence of upper respiratory tract infections and severity of asthma and lowers IgE antibody titers in atopic disease (1,53,54). In addition, in infants receiving scGOS, lcFOS, and pectin-derived oligosaccharides (pAOS), a preventive effect was found for development of atopic dermatitis (17).…”
Section: R Espiratory Syncytial Virus (Rsv) a Pneumovirus In The Familymentioning
confidence: 99%
“…19 GOS/FOS supplementation was also reported to induce a beneficial antibody profile. 39 GOS/FOS would reduce the total Ig response and modulate the immune response toward CMP, leaving the response to vaccination intact. 39 In practice, different supplements (prebiotics, lipids, nucleotides,.…”
Section: Prebiotics and Immune Parametersmentioning
confidence: 99%